HIFU for Bone Metastases and other Musculoskeletal Applications - Scipione, Roberto; Anzidei, Michele; Bazzocchi, Alberto; Gagliardo, Cesare; Catalano, Carlo; Napoli, Alessandro (Seminars in Interventional Radiology, 2018)
High-intensity focused ultrasound (HIFU) is a totally noninvasive procedure that has shown promising results in the management of numerous malignant and nonmalignant conditions. Under magnetic resonance or ultrasound guidance, high-intensity ultrasound waves are focused on a small, well-defined target region, inducing biologic tissue heating and coagulative necrosis, thus resulting in a precise and localized ablation. This treatment has shown both great safety and efficacy profiles, and may offer a multimodal approach to different diseases, providing pain palliation, potential local tumor control, and, in some cases, remineralization of trabecular bone. In musculoskeletal field, HIFU received FDA approval for treating bone metastasis, but its application has also been extended to other conditions, such as osteoid osteoma, desmoid tumor, low-flow vascular malformation, and facet joint osteoarthritis. This article illustrates the basic principles of HIFU and its main effects on biologic tissues with particular attention on bone, provides a step-by-step description of the HIFU procedure, and discusses the commonly treated conditions, in particular bone metastases.
Keywords: High-intensity focused ultrasound; bone metastases; osteoid osteoma; pain palliation; interventional radiology